Regularizing algorithms for constructing intermolecular potentials on the basis of experimental data - Anikeeva, N.V.; Yagola, A.G.; Kochikov, I.V.; Kuramshina, G.M. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
An algorithm for constructing intermolecular potentials on the basis of experimental data on temperature dependence of the second virial coefficient is proposed. The problem of constructing the intermolecular potential is solved on the class of convex-concave functions. It is shown that our approach allows one to restore potentials of intermolecular interaction accurately enough.